Multilevel reduced-order computational model in structural dynamics for the low- and medium-frequency ranges. (November 2015) - Ezvan, O.; Batou, A.; Soize, C.
Highlights: Novel methodology for constructing a multilevel ROM in structural dynamics. Numerous local elastic modes intertwined with the usual global elastic modes. Linear computational structural dynamics for the low- and medium-frequency ranges. Validation for an automobile structure. Abstract: This work deals with the dynamical analysis of complex structures composed of several structural levels and characterized by the presence of numerous local elastic modes intertwined with global modes, in the medium-frequency range as well as in the low-frequency range. For constructing the ROM, a family of global-displacements eigenvectors are calculated and are used instead of the classical elastic modes. Since it is also of importance to adapt the physical models (damping, level of uncertainties, etc.) to each one of the structural levels, a multilevel ROM is proposed. A validation is performed for an automobile complex structure.